MANFAAT DAN TUJUAN MENDONGENG DALAM MENINGKATKAN MINAT BACA ANAK USIA DINI DI BALAI LAYANAN PERPUSTAKAAN DPAD DAERAH ISTIMEWA YOGYAKARTA (DIY) - Apriani, Dea (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
Telling stories is often done by teachers for preschoolers. Storytelling has many benefits for preschoolers. As such, early childhood education needs to keep developing storytelling skills. This qualitative descriptive study will address the many advantages and goals of storytelling for kids, supported by bibliographical research. The findings of this study are as follows. Firstly, storytelling is the act of narrating made-up stories that don't truly teach the greatest moral lessons from history or the worst. Second, the goal of storytelling for young children is to build moral principles and good behaviour so that they can grow up balanced and with developed cognitive, emotional, and psychomotor skills. Thirdly, the advantages of storytelling for young children encompass improving focus, honing recall, enhancing language proficiency, stimulating curiosity in reading, elevating critical thinking abilities, and fortifying emotional bonds between educators and learners.